2011
DOI: 10.3397/1.3609820
|View full text |Cite
|
Sign up to set email alerts
|

Noise control strategies using composite porous materials – Simulations and experimental validations on plate/cavity systems

Abstract: This paper examines the potential of using composite porous materials to design robust noise control packages. Composite porous are meso-perforated porous materials in which perforations are filled with another porous material. The work presented here shows that the association of two carefully selected materials could lead to interesting combined properties of sound absorption and sound insulation. A canonical plate/cavity system excited with an internal acoustic source is chosen to illustrate the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…It is chosen to focus on the low frequency range, namely up to 600 Hz, where porous materials present low performances. The results presented here are comparable to those presented by Becot [4]. Numerical results show that the system exhibits two different behaviors depending on the frequency.…”
Section: Introductionsupporting
confidence: 88%
“…It is chosen to focus on the low frequency range, namely up to 600 Hz, where porous materials present low performances. The results presented here are comparable to those presented by Becot [4]. Numerical results show that the system exhibits two different behaviors depending on the frequency.…”
Section: Introductionsupporting
confidence: 88%
“…The influence of the double porosity mainly depends on the permeability contrast between the two porous materials. Usage of double porous material shows that an interesting compromise could be achieved by increasing the absorption and limiting the loss of sound insulation due to the presence of pores . The literature has also revealed the potential of these materials to design passive sound-absorbing solutions with good performances even at low frequencies .…”
Section: Resultsmentioning
confidence: 99%
“…Usage of double porous material shows that an interesting compromise could be achieved by increasing the absorption and limiting the loss of sound insulation due to the presence of pores. 45 The literature has also revealed the potential of these materials to design passive sound-absorbing solutions with good performances even at low frequencies. 46 The added absorption effect is due to a partial coupling between the acoustic fields in the two pore networks.…”
mentioning
confidence: 99%
“…It is also found that for the filler content of 1.4% of NS and NC sound absorption is the highest (Figure 7c). The increase in acoustic effect may be due to the large surface area of fillers at the PU-filler interface where the acoustic energy can be dissipated as heat energy [6]. Further in case of porous sound absorbers sound propagation takes place in a network of interconnected pores such that viscous and thermal interaction causes the acoustic energy to be dissipated and convert them into heat energy.…”
Section: Studies On Mechanical Propertiesmentioning
confidence: 99%